Studi Kelayakan Penentuan Lokasi Tempat Sampah Terpadu (TPST): (Studi Kasus di Desa Wawobili, Kabupaten Konawe Kepulauan, Sulawesi Tenggara) - Riqbal, Riqbal; Ndibale, Wa; Rosdiana, Rosdiana (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2024)
Waste is a complex and serious problem faced by many countries, both developing and developed countries. Government policies regarding waste processing need to be enforced so that this problem can be handled properly. One of them is by applying the principles of good environmental governance in waste processing. What is the suitability of the plan for selecting a location for the construction of an integrated waste processing site (TPST) in Wawobili Village, West Wawonii District according to SNI No. 03-3241-1994? The aim of this research is: to analyze the suitability of the location plan for the construction of an integrated waste processing site (TPST) in Wawobili Village, West Wawonii District according to SNI No. 03-3241-1994. The method used in this research is an exploratory method. Exploratory research is a research method that aims to map an object in relatively depth. From the results of research on determining the location of TPST in Wawobili Village, West Wawonii District, Konawe Islands Regency, Table 4.6 shows a level of suitability in determining the location of Integrated Waste Disposal Sites (TPST). The implication of this research is that it can determine the location point for the construction of an integrated waste collection site (TPST) where all the criteria are met except for the distance indicator to the settlement which does not meet the criteria.